Values and Perceptions of the Islamic and Middle Eastern Publics - Moaddel, M.; Moaddel, M. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2007)
Addressing values and politics in the Muslim world, this pioneering volume examines attitudes towards democracy and politics, self-expression and traditional values, convergence and divergence of values between the elite and the publics of Islamic and European countries.